Exploration of small molecules as inhibitors of potential BACE1 protein to treat amyloid cerebrovascular disease by employing molecular modeling and simulation approaches. - Zhizhong Wang; Zhiyong Li; Ailong Lin; Qing Zhang; Yingchun Chen; Bizhou Bie; Juanjuan Feng (PLoS ONE)
Amyloid cerebrovascular disease, primarily driven by the accumulation of amyloid-beta (Aβ) peptides, is intricately linked to neurodegenerative disorders like Alzheimer's disease. BACE1 (beta-site amyloid precursor protein cleaving enzyme 1) plays a critical role in the production of Aβ, making it a key therapeutic target. In the current work, a CNS library of ChemDiv database containing 44085 compounds was screened against the BACE1 protein. Initially, a structure-based pharmacophore hypothesis was constructed, followed by virtual screening, with the screened hits docked to the BACE1 protein to determine the optimal binding modes. The docking results were examined using the glide gscore and chemical interactions of the docked molecules. The cutoff value of -5 kcal/mol was used to select hits with high binding affinities. A total of seven hits were chosen based on the glide g score. Furthermore, the possible binding mechanisms of the docked ligands were investigated, and it was discovered that all seven selected ligands occupied the same site in the predicted binding pocket of protein. The bioactivity scores of the compounds demonstrated that the chosen compounds possess the features of lead compounds. The toxicity risks and ADMET features of the selected hits were anticipated, and four compounds, J032-0080, SC13-0774, V030-0915, and V006-5608 were chosen for stability analysis. The selected hits were extremely stable and strongly bound to the BACE1 pocket, and conformational changes caused by RMSD, RMSF, and protein-ligand interactions were assessed using MD modeling. Similarly, principal component analysis revealed a large static number of hydrogen bonds. The MM/GBSA binding free energies maps revealed a significant energy contribution in the binding of selected hits to BACE1. The binding free energy landscapes indicated that the hits were bound with a high binding affinity. Thus, the hits could serve as lead compounds in biophysical investigations to limit the biological activity of the BACE1 protein.